Ready, steady, switch! Limited evidence for the role of executive functions in bilingual language control in children - González, Elisabet García; Jylkkä, Jussi; Lehtonen, Minna (Cambridge University Press, 2025)
We investigated the extent to which executive functions (EFs) are recruited in language switching in children in a cued picture-naming (CN) task. We expected to find associations between CN and EF tasks measuring inhibitory control and shifting. Another goal was to compare parent-reported children's everyday language control ability at home with their switching ability in the CN task and EF performance. The participants were mostly 5-7-year-old Norwegian- Spanish and Finnish-Swedish-speaking children (N = 45). The analysis was preregistered. Unexpectedly, the primary accuracy analysis showed positive associations between CN switching costs and EF performance in only one of the EF tests, flanker, and CN mixing costs were predicted only by the color-shape switch costs. Children's everyday language control ability did not show consistent significant associations with lab measures. Our study provides weak evidence for the view that EFs are engaged in language control when children have some years of bilingual experience.